Mechanism Of Calculation Of Advertising Tax Reporting And Delivery At Pt Mega Nikmat Persada Nusantara Makassar - Moh. Yasin Noor; Lina Mariana; Adrian Adrian (Universitas Muhammadiyah Makassar, 2022)
This research was conducted at PT Mega favors Persada Nusantara Makasaar with the aim of knowing whether the process of calculating and reporting and depositing billboard taxes at PT Mega Nimat Persada Nusantara is in accordance with the provisions of Perwali Makassar No. 40 of 2015. The method used in this research is descriptive in which each data is collected and analyzed then conclusions are drawn and the type of research used is descriptive qualitative. in accordance with the existing regulations in Makassar